Location, Location, Location: How Vascular Specialization Influences Hematopoietic Fates During Development - Heck, Adam M.; Ishida, Takashi; Hadland, Brandon (Frontiers in Cell and Developmental Biology, 2020)
During embryonic development, sequential waves of hematopoiesis give rise to blood-forming cells with diverse lineage potentials and self-renewal properties. This process must accomplish two important yet divergent goals: the rapid generation of differentiated blood cells to meet the needs of the developing embryo and the production of a reservoir of hematopoietic stem cells to provide for life-long hematopoiesis in the adult. Vascular beds in distinct anatomical sites of extraembryonic tissues and the embryo proper provide the necessary conditions to support these divergent objectives, suggesting a critical role for specialized vascular niche cells in regulating disparate blood cell fates during development. In this review, we will examine the current understanding of how organ and stage-specific vascular niche specialization contributes to the development of the hematopoietic system.